2001
DOI: 10.1192/bjp.178.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviour in psychosis: Prevalence and predictors from a randomised controlled trial of case management

Abstract: Intensive case management does not appear to influence the prevalence of suicidal behaviour in chronic psychosis. Predictors identified in this study confirm some previous findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 19 publications
5
28
0
4
Order By: Relevance
“…The consequence of inhibited serotonin neurotransmission is lower inhibition of impulsive and aggressive behavior, which may trigger suicidal behavior. In line with two earlier investigations of depression symptoms and suicidality in psychotic patients (Walsh et al, 2001;Aguilar et al, 2003), our study also confirmed that suicidal patients had more pronounced depressive symptoms compared to non-suicidal patients, which was evident in higher HDRS-17 score. Suicidal patients may have less appetite, which in turn results in lower intakes of certain nutrients such as lipids and, hence, further intensifies vulnerability to depressive and suicidal patterns of behavior but we were not found correlation between lipid profiles and depressive symptoms and could not confirmed the hypothesis.…”
Section: Resultssupporting
confidence: 92%
“…The consequence of inhibited serotonin neurotransmission is lower inhibition of impulsive and aggressive behavior, which may trigger suicidal behavior. In line with two earlier investigations of depression symptoms and suicidality in psychotic patients (Walsh et al, 2001;Aguilar et al, 2003), our study also confirmed that suicidal patients had more pronounced depressive symptoms compared to non-suicidal patients, which was evident in higher HDRS-17 score. Suicidal patients may have less appetite, which in turn results in lower intakes of certain nutrients such as lipids and, hence, further intensifies vulnerability to depressive and suicidal patterns of behavior but we were not found correlation between lipid profiles and depressive symptoms and could not confirmed the hypothesis.…”
Section: Resultssupporting
confidence: 92%
“…None of the covariates were significant in either of the models except for RIN in the paired model (F 1,21 = 4.89, p = 0.038). We next determined whether lower GAD65 mRNA in schizoaffective subjects could be a consequence of factors which may be more commonly associated with that diagnosis than with schizophrenia (i.e., death by suicide (5862); use of antidepressants, benzodiazepines or sodium valproate at time of death (63,64); diagnosis of substance abuse or dependence at time of death (65,66)). None of these factors were disproportionally represented in schizoaffective disorder subjects relative to schizophrenia subjects (all χ 2 < 3.6, p > 0.06).…”
Section: Resultsmentioning
confidence: 99%
“…Patients without a history of inpatient admission were also found more likely to report suicidal ideation than their counterparts who had been previously admitted in hospital. Th is was unlike results from other studies that showed that patients who attempted suicide were nearly twice as likely to have been admitted multiple times (Walsh et al 2001). A possible explanation for this seemingly contradictory occurrence may be the fact that the study was carried out in a community mental health service, where facilities like the day hospital and community psychiatric nurse support are oft en off ered to patients aft er discharge from hospital, thereby reducing their risk.…”
Section: Discussionmentioning
confidence: 64%
“…Some authors restricted their research to certain diagnostics groups, example those with depression (Friedman et al 1983), schizophrenia (Johns et al 1986) or mania (Dilsaver et al 1994), and sought to provide the best predictors of suicidal ideation or suicidal behaviour in these patients. A previous suicide attempt has been shown to be the best predictor of suicidal behaviour (Leon et al 1990;Walsh et al 2001) and other factors like age, number of previous admissions and intensity of care have been highlighted in these studies (Walsh et al 2001). Self-harm with or without suicidal intent has also been shown to correlate with increased suicidal behaviour and completed suicide (Cavanagh et al 2003).…”
Section: Introductionmentioning
confidence: 97%